2018
DOI: 10.1007/978-3-319-91287-5_27
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-/HIF-1α-Driven Factors of the Tumor Microenvironment Impeding Antitumor Immune Responses and Promoting Malignant Progression

Abstract: The metabolic tumor microenvironment (TME) is characterized inter alia by critical oxygen depletion (hypoxia/anoxia), extracellular acidosis (pH ≤ 6.8), high lactate levels (up to 40 mM in heterogeneously distributed areas), strongly elevated adenosine concentrations (10-100 μM) and declining nutrient resources. These TME features are major drivers, e.g., for genetic instability, intratumor heterogeneity, malignant progression and development of resistance to conventional anticancer therapies. In this context,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 20 publications
0
108
0
Order By: Relevance
“…Previous studies have revealed that tumor hypoxia alters the composition and activity of tumor-associated immune cells, and that numerous immune cells with immunosuppressive activities are recruited to tumor tissues to form the immunosuppressive microenvironment (18,50,51). Under hypoxic conditions, tumor cells and macrophages secrete a variety of cytokines and chemokines, including C-C motif chemokine (CCL)22, CCL28 and IL-10, which results in the recruitment of CD4 + CD25 + FOXP3 + Tregs from peripheral blood to inhibit T cell-mediated antitumor responses (18,52,53). Hypoxia also promotes the recruitment of MDSCs (19).…”
Section: Hypoxia-induced Recruitment Of Immunosuppressive Cells and Rmentioning
confidence: 99%
“…Previous studies have revealed that tumor hypoxia alters the composition and activity of tumor-associated immune cells, and that numerous immune cells with immunosuppressive activities are recruited to tumor tissues to form the immunosuppressive microenvironment (18,50,51). Under hypoxic conditions, tumor cells and macrophages secrete a variety of cytokines and chemokines, including C-C motif chemokine (CCL)22, CCL28 and IL-10, which results in the recruitment of CD4 + CD25 + FOXP3 + Tregs from peripheral blood to inhibit T cell-mediated antitumor responses (18,52,53). Hypoxia also promotes the recruitment of MDSCs (19).…”
Section: Hypoxia-induced Recruitment Of Immunosuppressive Cells and Rmentioning
confidence: 99%
“…Cancer cells often suffer from hypoxia, nutrient (glucose and amino acid), and energy deprivation resulting from insufficient vasculature and blood supply [1]. These stress conditions are key factors imposed on proliferating tumor cells to trigger their malignant transformation and to enable them to overcome or escape antitumor immune surveillance and to avoid cellular senescence and apoptosis [2][3][4]. This results in tumor progression and aggressiveness, genetic instability, development of chemo-and radio-resistance, and poor prognosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the TME, MDSCs have extensive glycolysis due to the presence of hypoxia conditions. The glycolytic pathway of MDSCs is regulated by hypoxia inducible factor-1α (HIF-1α), which enhances the immunosuppressive function of MDSCs [ 25 , 26 , 27 , 28 ]. HIF-1α was found to be the main cause of the tumor microenvironment effect on the differentiation and function of MDSCs ( Figure 1 ) [ 25 ].…”
Section: Metabolism Of Mdscsmentioning
confidence: 99%